Analisis Manajemen Logistik Obat di Dinas Kesehatan Kabupaten Kolaka Tahun 2023 - Adewiah Sari; Nani Yuniar; Renni Meilahsari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Good logistics management of medicines is one of the factors so that medicines can be managed well. The pharmacy unit of the Kolaka District Health Service has problems with inadequate storage or storage of medicines and delays in the arrival of medicines. The aim of this research is to determine the Analysis of Drug Logistics Management at the Kolaka District Health Service. The research uses qualitative methods through in-depth interviews, observations and observation guides. The results of the research show that at the drug planning stage using the consumption method, drug procurement using an e-catalog system, drug storage is still not good because the warehouse is not large enough for drug storage. Suggestions for the Kolaka District Health Service.